Effect of biological, psychological, and social factors on maternal depressive symptoms in late pregnancy: a cross-sectional study - Chen, Xu; Liu, Meilin; Min, Fanli; Tong, Jiao; Liu, Yuan; Meng, Qian; Zhang, Teng (Frontiers in Psychiatry, 2023)
IIntroduction: Depression commonly occurs during pregnancy and has become a major public health concern. Depression not only affects the individual but also causes adverse consequences for families and children. However, little is known regarding the depression status and its influencing factors in women during late pregnancy in China. This study aimed to assess the prevalence of maternal depressive symptoms in late pregnancy during the coronavirus disease 2019 (COVID-19) pandemic and further explore the effect of biological, psychological, and social factors on depressive symptoms. Methods: An institution-based cross-sectional survey was conducted among eligible women in the late pregnancy stage and underwent prenatal examination at Lianyungang Maternal and Child Health Hospital in Jiangsu Province, Eastern China from December 2022 to February 2023. Data regarding depressive symptoms and biological, psychological, and social factors of the pregnant women were collected via a structured questionnaire. Chi-square test, Fisher’s exact tests, and binary logistics regression were used to analyze the data. Results: In total, 535 women in the late pregnancy stage were included in this study, 75 (14.0%) of whom exhibited depressive symptoms. A binary logistic regression analysis revealed that pregnant women who were multiparous (OR: 2.420, 95% CI: 1.188–4.932) and had moderate or severe insomnia symptoms (OR: 4.641, 95% CI: 1.787–12.057), anxiety (OR: 8.879, 95% CI: 4.387–17.971), high fear of COVID-19 (OR: 2.555, 95% CI: 1.255–5.199), moderate or severe family dysfunction(OR: 2.256, 95% CI: 1.141–4.461), and poor social support (OR: 2.580, 95% CI: 1.050–6.337) tended to show depressive symptoms. Conversely, pregnant women who received regular prenatal care (OR: 0.481, 95% CI: 0.243–0.951) and had good drinking water quality at home (OR: 0.493, 95% CI: 0.247–0.984) were more likely to avoid developing depressive symptoms. Conclusion: This study found that the prevalence of maternal depressive symptoms during late pregnancy was high and had multiple influencing factors. Thus, screening for depressive symptoms in women in the late pregnancy stage and providing special intervention programs are necessary, especially for those with risk factors.